NEW PUBLIC SERVICE PADA DESA WISATA CAFE SAWAH DI DESA PUJON KIDUL - Nurul Vidya Utami; Aos Kuswandi (Governance, 2022)
This study aims to determine the strategy used by Pujon Kidul Village to make Café Sawah a successful village-owned enterprise. The research method used applies qualitative methods with descriptive statistics. The results of the study show that the strategy applied by Cafe Sawah as a village-owned enterprise is to apply speed, solid, smart and smile which is done every day so that many visitors feel comfortable traveling at Café Sawah. The existence of Sapta Pesona which comes from the Tourism Awareness idea to always prioritize security, order, cleanliness, coolness, beauty, friendliness, and memories, as well as improving the performance of the apparatus by carrying out clean governance. In addition, the success of Cafe Sawah also comes from the panorama that is served by Pujon Kidul Village, which is able to spoil the eyes of visitors by turning a place that only lies with rice fields into one of the best destinations that must be visited when visiting Malang.